2017
DOI: 10.4103/2279-042x.200989
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone utilization review in a pediatric primary care setting

Abstract: Objective:One of the main problems facing public health providers and administrators in many countries is ensuring the rational use of high-cost drugs. In this regard, on-going process of medication use evaluation can be considered as a useful tool. In this study, we evaluated certain usage aspects of a highly-cost medication, that is, recombinant growth hormone (GH).Methods:This cross-sectional study conducted from August 2012 to August 2014. Children receiving GH ± gonadotropin releasing hormone (GnRH) analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…28 Another possibility is that HGH administration increases weight gain in patients, thereby raising their BMI. [29][30][31] Certainly, if this hypothesis were true, it would be consistent with current statistical trends of SCFE, namely the increased prevalence in obese children. 1 Our study found that the BMI percentage of the HGH cohort was lower than that of the No-HGH group, suggesting a potential BMI-independent relationship between SCFE onset and HGH administration.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…28 Another possibility is that HGH administration increases weight gain in patients, thereby raising their BMI. [29][30][31] Certainly, if this hypothesis were true, it would be consistent with current statistical trends of SCFE, namely the increased prevalence in obese children. 1 Our study found that the BMI percentage of the HGH cohort was lower than that of the No-HGH group, suggesting a potential BMI-independent relationship between SCFE onset and HGH administration.…”
Section: Discussionsupporting
confidence: 61%
“…Despite this, there is no current definitive indication for hormone sampling, which may be potentially implicated in SCFE development, even in the absence of other clinical symptoms or stigmata of underlying endocrinopathy 28 . Another possibility is that HGH administration increases weight gain in patients, thereby raising their BMI 29–31 . Certainly, if this hypothesis were true, it would be consistent with current statistical trends of SCFE, namely the increased prevalence in obese children 1 .…”
Section: Discussionmentioning
confidence: 87%
“…Factors unique to the wider literature included: fear of side effects/long-term complications [15, 27, 35], the preference [36] and convenience of an injection device (ease of use, technical handling, and storage) [10, 24, 36], and accessibility of the rhGH distributing pharmacy [15] as well as sociodemographic factors (more specifically, the level of parental school education) [24, 29, 34, 38]. …”
Section: Discussionmentioning
confidence: 99%